Evaluation of Ashitaba (Angelica keiskei) Crackers Formulations as α-Glucosidase Enzyme Inhibitors - Khoiriyah, Romyun Alvy; Marliyati, Sri Anna; Ekayanti, Ikeu; Handharyani, Ekowati (Media Gizi Indonesia, 2024)
One of the global health issues is diabetes mellitus, characterized by elevated blood glucose levels. The absorption of glucose in the body occurs through the digestion of carbohydrates by the enzyme α-glucosidase, which is responsible for hydrolyzing carbohydrates into sugar. Ashitaba (Angelica keiskei) is a  herbal plant from Japan and has long been utilized in traditional medicine for its various health benefits and preventive properties against multiple diseases. This plant has also been cultivated in Indonesia, including Trawas Mojokerto, East Java. This study aims to develop ashitaba crackers and evaluate their potential α-glucosidase inhibitory activity to develop safe and effective natural products to assist in managing diabetes more efficiently. This research was conducted from July to September 2022. Two formulations of fresh ashitaba leaves were used (12% CAST 1 and 18% CAST 2 of 100 g of flour). Based on the results of this research, chemical composition tests showed that the carbohydrate and dietary fiber content in CAST 1 were higher than those in CAST 2. Protein, lipid, water, and ash content in CAST 2 had higher values than in CAST 1. Flavonoid content and inhibitory activity test results of ashitaba crackers showed significant differences between the two formulation groups regarding flavonoid content and percentage inhibition against the α-glucosidase enzyme. Both flavonoid content and inhibitory activity in CAST 2 were higher than in CAST 1. Ashitaba crackers with the best formulation in this study, based on flavonoid levels and their ability to inhibit α-glucosidase enzyme, were identified as CAST 2.